Community Empowerment in Making Galactagogue Herbal for Breastfeeding Mothers - Murwati, Murwati; Nutrisia Aquariushinta Sayuti; Wahyuni, Sri; Octa Maulidia, Syifa; Fathonah, Rosi; Alnadela, Jensi (Universitas Pendidikan Ganesha, 2024)
The bitter taste of uyup-uyup, an herbal herb that promotes breast milk, makes breastfeeding mothers in Jarum Village, Klaten reluctant to consume it, even though uyup-uyup has the potential to prevent stunting in babies. This research aims to empower the community by increasing knowledge about the benefits of uyup-uyup in maintaining health through counseling and assistance in making UEENAK uyup-uyup products that are more delicious and practical. This study uses a one-group pre-post test design which will be carried out in 2024, involving 45 subjects consisting of health center officials, PKK members, health cadres, and breastfeeding mothers. Knowledge data were collected using questionnaires and analyzed using the Wilcoxon test to see changes in knowledge before and after the intervention. The results showed a significant improvement in the subject's knowledge with a difference in pretest and posttest scores (61.33(14,937) vs 75.78(10,333), p-value=0.001). In addition, the subject stated that UEENAK uyup-uyup products are tastier and easier to make. This study concluded that counseling and mentoring activities have succeeded in empowering the community, which motivates them to explore other herbs to prevent stunting and increase breast milk production. UEENAK uyup-uyup products have the potential to be developed as commodities of economic value.